A topo-graph model for indistinct target boundary definition from anatomical images. (June 2018) - Cui, Hui; Wang, Xiuying; Zhou, Jianlong; Gong, Guanzhong; Eberl, Stefan; Yin, Yong; Wang, Lisheng; Feng, Dagan; Fulham, Michael
Highlights: A novel topographic representation to extract multiple-level regional relations for adjacent tissues with similar intensity distributions. A new graph with nesting branches for separation and geodesic edges for boundary identification. Validations on NSCLC CT, liver CT, breast and abdominal ultrasound images. Improved accuracy over graphs with pixel and/or regional, neighboring/radial connections. Abstract: Background and Objective: It can be challenging to delineate the target object in anatomical imaging when the object boundaries are difficult to discern due to the low contrast or overlapping intensity distributions from adjacent tissues. Methods: We propose a topo-graph model to address this issue. The first step is to extract a topographic representation that reflects multiple levels of topographic information in an input image. We then define two types of node connections - nesting branches (NBs) and geodesic edges (GEs). NBs connect nodes corresponding to initial topographic regions and GEs link the nodes at a detailed level. The weights for NBs are defined to measure the similarity of regional appearance, and weights for GEs are defined with geodesic and local constraints. NBs contribute to the separation of topographic regions and the GEs assist the delineation of uncertain boundaries. Final segmentation is achieved by calculating the relevance of the unlabeled nodes to the labels by the optimization of a graph-based energy function. We test our model on 47 low contrast CT studies of patients with non-small cell lung cancer (NSCLC), 10 contrast-enhanced CT liver cases and 50 breast and abdominal ultrasound images. The validation criteria are the Dice's similarity coefficient and the Hausdorff distance. Results: Student's t -test show that our model outperformed the graph models with pixel-only, pixel and regional, neighboring and radial connections ( p -values <0.05). Conclusions: Our findings show that the topographic representation and topo-graph model provides improved delineation and separation of objects from adjacent tissues compared to the tested models. Graphical abstract: